Serum homocysteine levels are associated with progression of childhood vitiligo - Hengpo ZHANG; Haiyan CHANG; Dalei ZHANG; Weili HAO; Bingqin CAO; Jing LI; Junbo DU; Yun LI (editoiral office of Journal of Diagnosis and Therapy on Dermato-venereology, 2023)
Objective To investigate the significance of serum homocysteine(Hcy) levels and their association with disease state in childhood vitiligo. Methods Serum Hcy levels were measured in 164 childhood vitiligo and 164 healthy controls. Vitiligo subjects were grouped into stable, progressive, rapid progressive and non-rapid progressive groups, and serum Hcy levels were compared among these groups. The receiver operating characteristic (ROC)curve was applied to estimate the predictive efficacy of these parameters. Results Hcy levels were significantly higher in patients with vitiligo than in healthy controls(t=15.71, P<0.001).Hcy levels were significantly higher in progressive vitiligo than in stable vitiligo (35.89±14.70 vs 17.86±5.13, t=10.38, P<0.001). The area under ROC curve (AUC) of Hcy was 0.94, and the optimal cut-off point of Hcy levels was 22.40 in patients with progressive vitiligo, with the sensitivity and specificity of 90.48% and 82.50%, respectively. Hcy levels were significantly higher in patients with rapid progression than in those with non-rapid progression (t=9.40, P<0.001). Hcy levels were lower after the treatment vs baseline levels (8.35±3.24 vs 35.89±14.70, t=16.76, P<0.001). Conclusions Serum Hcy levels are associated with the progression of vitiligo in children. Hcy levels are a potential predictor for the progression of vitiligo.